Autoimmune neutropenia: a rare complication of allogeneic hematopoietic stem cell transplantation? - Benítez Carabante, María Isabel; Morell Daniel, Mariona; Uría Oficialdegui, María Luz; Casanovas López, Enric; Panesso Romero, Melissa; Alonso García, Laura; Díaz-de-Heredia, Cristina (Frontiers in Immunology, 2025)
BackgroundAutoimmune cytopenias (AIC) are rare complications of allogeneic hematopoietic stem cell transplantation (HSCT). Autoimmune neutropenia (AIN) is the least common type of AIC, and data on its incidence, risk factors and prognosis are scarce. This study aims to describe the incidence of AIN, its potential risk factors, and its clinical outcomes.Study designThis retrospective study included children who underwent a first allogeneic HSCT between 2015 and 2022. Patients with primary graft rejection were excluded. The primary endpoint was the incidence of AIN. Secondary endpoints included secondary graft failure (GF), overall survival (OS), and event-free survival (EFS).ResultsA total of 208 patients were included, 30 of whom were diagnosed with AIN. The median time from HSCT to AIN diagnosis was 104 days, with a cumulative incidence of 8.73% (95%CI, 5.6-13.51) at 6 months and 14.74% (95%CI, 10.47-20.55) at 2 years after HSCT. No risk factors were found to be associated with AIN. The cumulative incidence of secondary GF at 2 years was 13.75% (95%CI, 5.38-32.68) in patients with AIN compared to 4.73% (95%CI, 2.39-9.25) in patients without AIN (p=0.06). There were no differences in terms of OS or EFS between patients with AIN and patients without AIN, with 3-year OS of 82.9% (95%CI, 63.6-92.5) vs 81.8% (95%CI, 75.26–86.77) (p=0.64) and 3-year EFS of 72.8% (95%CI, 52.8-85.4) vs 79% (95%CI, 72.2-84.31) (p=0.67). We identified two patients with specific human neutrophil alloantigen antibodies (anti-HNA), one of whom had a secondary graft failure.ConclusionsAIN may be a more frequent complication in post-HSCT pediatric patients than previously reported. Patients with AIN may be at a higher risk of secondary GF, but whether the risk of secondary GF is an important issue in patients with AIN needs to be explored in larger cohorts of patients. The study of specific anti-HNA in high-risk AIN patients should be considered.